Robust super-twisting sliding mode controller for the lateral and longitudinal dynamics of rack steering vehicle - Norsharimie Mat Adam; Addie Irawan; Mohd Ashraf Ahmad (Institute of Advanced Engineering and Science, 2022)
Inertia phenomenon in steering vehicle is major factor that allow oversteering incident in which come from the insufficient steering and slip control over the vehicle itself. The efficient and robust control system is required to consider both precision and stability of the vehicle for better manuevering especially in cornering road. Therefore, this research has taken the initiative to contribute a better solution for vehicle control according to the mentioned problem and situation with a proposed robust super-twisting sliding mode control (ST-SMC) by simplified torque on wheel and steering angle input with decoupling lateral and longitudinal errors. This control technique approach to allow coping with the issue by reducing forces and inertia for optimum speed at the cornering period and with the almost precise steering positioning. The dynamic model of rack steering vehicle (RSV) is used as the model plant and the proposed control system is simulated for verification. The results shows that the proposed ST-SMC offers improved performance in terms of speed increase time and vehicle stability that gives impact to the RSV being skidded or collided to any obstacles during cornering period.